Posredni psihosocialni dejavniki tveganja za zdravje zaposlenih v bolnišnici - Bizjak, Jana (Obzornik zdravstvene nege, 2021)
Introduction: Employee health is affected by psychosocial risk factors that include direct and indirect factors. The aim of the study was to determine the extent to which indirect risk factors in the workplace impact the psychophysical health of employees. Methods: A descriptive cross-sectional survey was administred to 112 out of 994 randomly selected employees in a general hospital. The measurement instrument used was a standardized questionnaire 'Managing Psychosocial Risks and Absenteeism' (Cronbach alfa = 0.915). We used quantitative data analysis to determine the relationship between the variables and regression analysis to determine the power of the independent variables on employee psychophysical health. Results: The results have shown that all indirect psychosocial risk factors analized are related to employees' psychophysical health: attitudes towards work, interpersonal relationships, organizational culture, personality traits, career development, work-life boundaries, and self-care. Psychophysical health is predicted by attitude to work and personality traits (R2 = 0.40). Discussion and conclusion: Respondents most commonly reported pain in shoulder muscles, neck and / or upper limbs, as well as health-related symptoms such us being overworked and tired. Among the indirect risk factors, employees health was significantly influenced by personal characteristics and attitude towards work, or perception of problems as challenges and positive attitude towards work outcomes. The results can serve the management of the hospital, which could reduce the burden on employees by means of good work organization and better working conditions.
Keywords: delovno okolje; medicinske sestre; nurses; nursing; psihofizično zdravje; psychophysical health; risk factors; tveganje; work environment; zdravstvena nega